If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4 + -1h) = 5h (4 * 3 + -1h * 3) = 5h (12 + -3h) = 5h Solving 12 + -3h = 5h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-5h' to each side of the equation. 12 + -3h + -5h = 5h + -5h Combine like terms: -3h + -5h = -8h 12 + -8h = 5h + -5h Combine like terms: 5h + -5h = 0 12 + -8h = 0 Add '-12' to each side of the equation. 12 + -12 + -8h = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -8h = 0 + -12 -8h = 0 + -12 Combine like terms: 0 + -12 = -12 -8h = -12 Divide each side by '-8'. h = 1.5 Simplifying h = 1.5
| 8n-13=5n+5 | | 12m+12(12m)=108 | | 8-(2y-7)=3-3y | | -1(-1x+3)=3(-x+3) | | X+3(x-4)= | | 8(x+2)=2x+16 | | y=5/3(-1)-3 | | -2.3=-5.1 | | 5x-10=-x^2+2x+18 | | 2x^2-28x-58= | | 5x-27=4x+8 | | .83u+4=.16u-2 | | 17b+4=-41/2 | | 12y(y+2)+5=2y-1 | | 11x-6+2x-4=10x-2+2x | | 3x-x+4=4(2x-1) | | -2x+1.5=4.5 | | 11x-6+2x-4=10x-2+x | | 8y+6=37-9 | | 4x-8y=-40 | | -1.5x+3=2(2x-3) | | 1/2(x-4/5)=3/5 | | 7w-19=8-x | | 0.3333333333+2z=-0.8333333333 | | 10+20b=200 | | 2(4x-5)-3(6-2x)=0 | | 78=3c+112-c+4 | | 18y-32=3y | | (6y+3)-(8y-4)= | | 0.5(x+1)1=0.2 | | 7(1x-7)=-70 | | (2x-5)(x^2+4x-6)=0 |